Report of deputation to Minister of Health on "A National Health Service"...
1945-03 1945 1940s 8 pages -4- statement had been made at two meetings of the Advisory Committee under the Disabled Persons (Employment) Act. Not only the principle of rehabilitation should be accepted as part of the service but it should be made so prominently important that at least there would be no dubiety in respect to it. Rehabilitation meant making everybody fit either to do their own job or some other job and they should never become a casualty until there was absolutely no alternative to it. In regard to hospitals, some of the information given by the Minister seemed to have a very good object in view but he would rather refrain from commenting on it because it might need rather a lot of thought. If the purpose of the Ministry was to make the administrative and operative side of the hospitals more effective, then they would get no opposition from the T.U.C. The T.U.C. did not agree with voluntary hospitals even on the basis suggested in the White Paper but it was felt that with their long history and associations at least the provision in the White Paper had something to be said in support of it. Negotiations had of course been going on with the British Hospitals Association and their point of view was well known. In that connection the deputation would like an assurance that the part of the White Paper dealing with hospitals, when it came to be put into operation, would not be weakened in any way. Nobody wanted to throw stones at all the good work that the hospitals had done for a long time but it was felt that hospitals should not have to rely on voluntary support. It was feared that there might be a danger of a conflict existing between voluntary hospitals and those of local authorities with the former having the backing of the B.M.A. and the latter having the backing of the local townspeople in various ways. That position should be avoided because the sufferers from such a conflict would be the patients who had to use the hospitals. A high standard of nursing, ambulance work and other things was essential for good hospital treatment and the deputation hoped that the detailed question of the ancilliary services might be discussed with Sir Wilson Jameson or some other appropriate representative in order that every branch of the service should be properly represented and organised on the best possible lines. Industrial health was a question in which every worker had a vital interest because at the present time the industrial medical service was operating in a most unsatisfactory manner. Most works doctors were employed by the employer and there was no confidence so far as the worker was concerned in them. There had been a reluctance on the part of most young working people to undergo medical examinations because they felt failure to pass the doctor would mean losing their job. Mr. Allen then referred to the example in the railway industry where the employers took only the view of the doctor whom they themselves employed, in a decision on any case. The cure for that position was an industrial medical service as part of the whole scheme. The employer should not have the alternative as to whether he would employ a doctor or not. If the industrial medical service was made part of the general scheme, the confidence of the workpeople would most probably be obtained. Mr. Willink dealt with the following points made by Mr. Allen. The Combination of Private and Public Practice. The Ministry did not feel at the present stage that they were in a position to legislate for a prohibition on any doctor making a private arrangement with any patient for private treatment. The next question was as to whether the two should be separated 292/847/3/118